1978
DOI: 10.1111/j.2044-8341.1978.tb02441.x
|View full text |Cite
|
Sign up to set email alerts
|

The melancholy marriage: An inquiry into the interaction of depression.

Abstract: In this domain we are aiming to measure the degree and quality of attentiveness or mutuality that marital partners show for each other in a relationship where constraints or limitations have been applied to the interacting system through the emergence of depressive symptoms in one or both partners. Raush, Barry, Hertel & Swain (1974) have formulated the interactive dynamics of a disturbed marital system and see contextual variables such as depressive behaviour as enhancing or diminishing the meaningful quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 0 publications
3
27
0
1
Order By: Relevance
“…In one study, for example, the foci of investigation were the patterns of communication between spouses The results of studies combined in book The Melancholy Marriage were also published separately. Four of the five individual references are listed in Table 5; the other is Hooper, Roberts, Hinchcliffe, and Vaughn (1977).…”
Section: Marital Adjustmentmentioning
confidence: 99%
“…In one study, for example, the foci of investigation were the patterns of communication between spouses The results of studies combined in book The Melancholy Marriage were also published separately. Four of the five individual references are listed in Table 5; the other is Hooper, Roberts, Hinchcliffe, and Vaughn (1977).…”
Section: Marital Adjustmentmentioning
confidence: 99%
“…A further complicating factor is that not only does the quality of the marital relationship affect the onset of depression, but episodes of depression have a long-term detrimental effect on the quality of the relationship. Depressed women tend to ruminate more than depressed men in response to their depressed mood, and depressed husbands have a greater ability to cause depressed mood in their wives than the converse situation (Hinchcliffe et al, 1978). One study showed that marital dysfunction was still apparent up to 48 months after depressed women had lost their symptoms (Rounsaville, 1980) but no comparable group of men have been studied.…”
Section: Iv) Marital Statementioning
confidence: 99%
“…Similarly, spousal depression is a reliable and robust predictor of marital dissatisfaction (Beach & Oleary, 1993; Beach, Smith, & Fincham, 1994; Hinchliffe, Hooper, Roberts, & Vaughan, 1978; Whisman, Uebelacker, Tolejko, Chatav, & McKelvie, 2006). The relationship between depression and marital distress is most likely bidirectional and influenced by characteristics of the depressive disorder, including its course, which most commonly is episodic and recurrent as well as gender differences in its expression (Coyne & Benazon, 2001).…”
mentioning
confidence: 99%